Corruption Eradication Commission’s Wiretapping: Should it Need Permit by Supervisory Council? - Suastuti, Eny; S.B. Yuherawan, Deni; Arif Pribadi, Firman (International Journal of Psychosocial Rehabilitation, 2020)
This research is about the authority of wiretapping by the Indonesian Corruption Eradication Commission (KPK) and the existence of a Supervisory Council as the giver of wiretapping permission. At the time the new KPK Law was enacted, many responses had been raised by legal scholars who had caused a kind of polemic around the substance of "wiretapping," which illustrates an ideal law. The purpose of this study is to find out the rationale for the existence of a Supervisory Council in granting wiretapping permission, which is the basis of the polemic. The results of the study concluded that the obligation to obtain permission from the Supervisory Council is contrary to the principle of independence from the KPK, namely as a state institution that is free from the influence of any power in carrying out its duties and authorities The researcher recommends that the wiretapping permit mechanism be an integrated task of the KPK in conducting investigations. Permission to tap from the Supervisory Council will hamper KPK performance. Considering the Supervisory Council was formed to oversee the implementation of the duties and authority of the KPK not included in the technical case handling.